Profile Literasi Sains dan Kesadaran Budaya Siswa serta Kebutuhan terhadap Bahan Ajar IPA Terintegrasi Potensi Lokal Petis Berbasis STEAM-PBL di Kabupaten Sumenep Syiah Kuala (Coba Dulu) - Kamila; Insih Wilujeng; Laifa Rahmawati (Jurnal Penelitian Pendidikan IPA, 2024)
Science literacy is a must have ability for students in the 21st century and cultural awareness is needed so that students can selectively choose outside cultures. However, in Indonesia science literacy and cultural awareness are low. This study aims to determine the profile of science literacy and cultural awareness of students and the need for STEAM-PBL-based local potential integrated science teaching materials. This research is a descriptive research. The research sample amounted to 93 junior high school students in 3 Sumenep District schools selected by purposive random sampling technique. Data collection used tests to measure science literacy, questionnaires to determine cultural awareness and need STEAM-PBL-based local potential “petis” integrated science teaching materials. Data analysis using quantitative descriptive analysis techniques. The results showed; 80.65% of students were in the low category and 19.35% were in the medium category, the lowest student ability was to explain phenomena scientifically; 88.17% of students' cultural awareness was in the low category and 11.83% of students were in the medium category. Based on the results of the study, it is concluded that students' science literacy and cultural awareness are low and it is necessary to develop teaching materials integrated with the local potential of STEAM-PBL-based petis.